FIRM SIZE, AND FIRM VALUE ON CORPORATE SOCIAL RESPONSIBILITY IN INDONESIA (Survey on Bank Mandiri and Bank Mandiri Syariah Year 2014-2018) - ERSI SISDIANTO; Ainul Fitri (Journal of Islamic Business and Economic Review, 2020)
This study aims to determine the effect, firm size, and firm value on social responsibility coprorate. This study uses a case study approach. Object of this research is Bank Mandiri and Bank Syariah Mandiri research data derived from financial statements and Sustainability report, Bank Mandiri and Bank Syariah Mandiri in 2014-2018. SPSS 24 is used as a tool to analyze the data. The results show that firm size and firm value positive and significant impact on corporate social responsibility. Limitations of this study are only discussing how big the influence of firm size and firm value to corporate social responsibility, as well as  the number of samples and the population studied only Bank Mandiri and Bank Syariah Mandiri thus opening opportunities for new researchers with the same theme. The implications of this study are expected to be able to add to their repertoire of knowledge relating to the influencefirm size, and firm value on corporate social responsibility in banking in Indonesia.